Bianchi type III and Kantowski-Sachs cosmological models in Lyra geometry - Singh T.; Singh G.P. (My University, 2025)
The cosmological models for Bianchi type III and Kantowski-Sachs space-time within the framework of Lyra geometry are obtained. The physical behaviour of the models have also been discussed. © 1991 Kluwer Academic Publishers.